ETHICAL AND LEGAL DILEMMAS IN HEALTH INFORMATION DELIVERY: A STUDY ON TRANSPARENCY, MISINFORMATION, AND LEGAL LIABILITY ON DIGITAL PLATFORMS - Handojo Dhanudibroto; Gunawan Widjaja (ADISAM PUBLISHER, 2025)
This study explores the ethical and legal dilemmas in the delivery of health information on digital platforms, focusing on three main aspects: transparency, misinformation, and legal liability. In the digital age, quick and easy access to health information should help people make better decisions. However, a lack of transparency and the spread of misinformation can be detrimental to public health. This study emphasises the importance of transparency in information delivery to build public trust, while identifying misinformation as a serious threat to public health. The study also discusses the legal responsibility that information providers and digital platforms have to ensure the information provided is valid, accurate and based on scientific evidence. With a combination of strict regulations and strict law enforcement, it is hoped that a safer and more reliable information environment can be created for the public